Covid19, Mucociliary Clearance And Mechanisms of Beneficial Effects of Various Yoga Practices - Patel, Jignesh; Mandlik, Vishwas; Mandlik, Gandhar (International Research Journal of Ayurveda & Yoga, 2021)
The Coronavirus Disease 2019 (COVID19) outbreak is one of the biggest pandemics reported in the history. Widespread prevalence of COVID19 have not only caused the respiratory consequences, but also psychological effects because of its fear. Severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) is the virus responsible for COVID19 and have been reported to cause impairment in mucociliary clearance (MCC) as a result of damage to the ciliary layer of respiratory epithelium. Because MCC is one of the important defense process of respiratory system, impairment of MCC could be one of the important mechanisms of progression of COVID19. Yoga is a multidimensional system of practices for physical, mental, and spiritual health popularly practiced all over the world for physical and mental well-being. This article summarizes various components of COVID19, effect on mucociliary clearance, role of nitric oxide and various mechanisms of beneficial effects of yoga asana, pranayama, mantra chanting and meditation for prevention and treatment of COVID19.